Hyperoxia alters the mechanical properties of alveolar epithelial cells - Roan, Esra (American Physiological Society, 2012)
Patients with severe acute lung injury are frequently administered high concentrations of oxygen (>50%) during mechanical ventilation. Long-term exposure to high levels of oxygen can cause lung injury in the absence of mechanical ventilation, but the combination of the two accelerates and increases injury. Hyperoxia causes injury to cells through the generation of excessive reactive oxygen species. However, the precise mechanisms that lead to epithelial injury and the reasons for increased injury caused by mechanical ventilation are not well understood. We hypothesized that alveolar epithelial cells (AECs) may be more susceptible to injury caused by mechanical ventilation if hyperoxia alters the mechanical properties of the cells causing them to resist deformation. To test this hypothesis, we used atomic force microscopy in the indentation mode to measure the mechanical properties of cultured AECs. Exposure of AECs to hyperoxia for 24 to 48 h caused a significant increase in the elastic modulus (a measure of resistance to deformation) of both primary rat type II AECs and a cell line of mouse AECs (MLE-12). Hyperoxia also caused remodeling of both actin and microtubules. The increase in elastic modulus was blocked by treatment with cytochalasin D. Using finite element analysis, we showed that the increase in elastic modulus can lead to increased stress near the cell perimeter in the presence of stretch. We then demonstrated that cyclic stretch of hyperoxia-treated cells caused significant cell detachment. Our results suggest that exposure to hyperoxia causes structural remodeling of AECs that leads to decreased cell deformability.